2021
DOI: 10.3390/children8020098
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Interrelation of Physical Activity, Screen Time and Health-Related Quality of Life in Children and Adolescents in Germany: Results of the Motorik-Modul Study

Abstract: Reduced physical activity (PA) and prolonged screen time (ST) negatively influence health-related quality of life (HRQoL), a protective factor against illness and mortality. Studies addressing the relationship between PA, ST, and mental health in youth are scarce, especially in times with high mental health burdens like the COVID-19 pandemic. The purpose of this examination was to investigate whether PA, ST, and HRQoL before COVID-19 predict PA, ST, and HRQoL during the COVID-19 pandemic. Participants from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
88
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 65 publications
14
88
0
7
Order By: Relevance
“…Regarding the instruments used to evaluate the HRQoL, four different scales were used to evaluate the HRQoL of children and adolescents: KIDSCREEN-10 index, the SF-36, the Pediatric Quality of Life Inventory Questionnaire, and a Likert Scale (0–10). Three articles explicitly stated that used language validated versions [ 16 , 22 ] whereas the other three articles only described the questionnaire in their article [ 15 , 17 , 18 ]. To summarize, three articles reported that COVID-19 significantly reduced the HRQoL of children and adolescents [ 15 , 16 ], two articles did not find a significant impact [ 17 , 18 ], and one article did not report statistical comparison between pre- and post-pandemic data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the instruments used to evaluate the HRQoL, four different scales were used to evaluate the HRQoL of children and adolescents: KIDSCREEN-10 index, the SF-36, the Pediatric Quality of Life Inventory Questionnaire, and a Likert Scale (0–10). Three articles explicitly stated that used language validated versions [ 16 , 22 ] whereas the other three articles only described the questionnaire in their article [ 15 , 17 , 18 ]. To summarize, three articles reported that COVID-19 significantly reduced the HRQoL of children and adolescents [ 15 , 16 ], two articles did not find a significant impact [ 17 , 18 ], and one article did not report statistical comparison between pre- and post-pandemic data.…”
Section: Resultsmentioning
confidence: 99%
“…To summarize, three articles reported that COVID-19 significantly reduced the HRQoL of children and adolescents [ 15 , 16 ], two articles did not find a significant impact [ 17 , 18 ], and one article did not report statistical comparison between pre- and post-pandemic data. Differences between girls and boys were explored in two articles [ 16 , 22 ] and non-significant differences were observed in the effect of the COVID-19 pandemic on the HRQoL. The impact of COVID-19 on the different dimensions of HRQoL was only analyzed in one study [ 16 ], showing that COVID-19 has negatively affected functional capacity, physical aspect, general health status, vitality, social aspects, emotional aspects, and mental health in both children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allerdings zeigte sich auch, dass ein hohes Ausmaß an Bildschirmzeit vor der Pandemie nicht nur positiv mit der Bildschirmzeit während der Pandemie korrelierte, sondern auch einen negativen Einfluss auf das Bewegungsverhalten während der Pandemie hatte. Im Gegensatz dazu korrelierte die gesundheitsbezogene Lebensqualität vor der Pandemie bei Kindern unter 10 Jahren und Mädchen insgesamt positiv mit der körperlichen Aktivität während der Pandemie (Wunsch et al, 2021). Brand et al (2020) zufolge neigten unter knapp 13.700 Teilnehmer aus 18 Ländern die vor dem Lockdown weniger aktiven Personen dazu, ihre Trainingshäufigkeit während des Lockdowns zu steigern.…”
Section: Veränderungen Des Bewegungsverhaltensunclassified
“…People were allowed to leave their houses for very limited needs (mainly job or urgent medical needs) [1]. Therefore, urban circulation, as well as outdoor activities, were minimized, leading to an increase in children's sedentary home life with health's implications [2,3]. The locking down resulted, among other issues, also in a sharp decrease in admissions to the emergency departments (ED), including the pediatric ones (pED).…”
Section: Introductionmentioning
confidence: 99%